A survey on breastfeeding practices at Dr. Pirngadi Hospital Medan - Adi Sutjipto; Djaman Purba; Nasril Nazir; M. D. Purba; Helena Siregar (Indonesian Pediatric Society, 1981)
From August up to December 1978 a survey had been carried out on breast milk feeding in children of 0-2 years treated in the Departement of Child Health, Medical School, University of North Sumatera, Medon. The method applied was by filling questionnaires.The results were as follows: from 65 children ill vestigated, 28 (43.1%) drank breast milk, 14 (21,5%) breast milk + artificial milk, 20 (30.8%) artificial milk and 3 (4.6%) did not get any milk.The time of starting artificial milk as additional milk feeding was found highest (33.3%) at the age 3 -6 months. The older the child the less the percentage of breast milk.